Estudo do Desempenho Térmico de Ferramentas de Corte Revestidas a partir da Obtenção da Solução Analítica de um Modelo Térmico de Condução de Calor 3D Transiente Dupla Camada - Oliveira, Gabriela Costa (2019)
The technological evolution of the production of tools led to the development and application of tool coatings facilitating the frictional cutting through the performance in the tribological mechanisms. One of the main functions of the coatings is to provide less wear of the tool, but the thermal insulation characteristics is another desired effect. This work is dedicated to the development of mathematical tools for the study of the thermal behavior of coated tools during the simulation of an orthogonal cutting process. In this sense, analytical solutions were developed in conjunction with the TFBGF(transfer function based Green's functions) inverse technique for estimating the heat flux generated at the coated tool interface. We present solutions of two direct problems related to the coated tool: a simpler thermal problem, 1D transient two-layer for a better understanding of the development of the solution methodology and the 3D transient two-layer problem that simulates the problem of orthogonal machining. This work presents the TFBGF inverse technique and the proposal of adaptation to two-layer problems. The solutions of the related direct problems, 1D and 3D, were verified to guarantee the numerical implementation of the solutions. Analysis of the influence of the thickness and the thermal properties of the coating on two-layer samples are also presented. The influence of the thermal properties of various types of coating, the temperature variation in the tool piece interface, the coating and substrate interface and the generation of heat generated at the interface were studied. Obtaining the analytical solution of a transient 3D two-layer partial heating problem represents a major contribution of this work since this solution is not available in the literature. The adaptation of the TFBGF technique to two-layer domains also proves to be a powerful tool in the study of coated materials.